Pengembangan Prototipe Alat Pengukur Medan Magnet Menggunakan Sensor Magnetik 49E - Rechan Zahrotun Nur; Nina Siti Aminah; Akfiny Hasdi Aimon (Jurnal Fisika Unand, 2024)
The magnetic field is an interesting physical phenomenon and found in everyday life. Many currents technological developments are applications of the magnetic field concept, such as electronics, electric motors, fast trains, and others. In this research, a prototype for measuring magnetic fields was developed with a physics instrumentation system. This prototype can be used for experimental measurements of magnetic fields for physics lecture in the school. It was found that a magnetic field measurement tool could be made using a physics instrumentation system. So, this tool can be used as an experimental medium for measuring the magnitude of the magnetic field in permanent magnet and wires carrying electric current. The prototype was consisted a 49E magnetic sensor. It is hoped that the prototype can replace the Gaussmeter or Teslameter which are relatively expensive. The prototype magnetic field measuring instrument was calibrated by comparing the magnetic field strength measured by the 49E sensor with the Lutron GU-3001 Gaussmeter. Measurements are observed at the centre of the object and parallel to the position of the measuring instrument. The results of the measurements show that the average magnetic field strength on the Gaussmeter and 49E sensor is 246.7 μT and 487.3 μT for permanent magnet and 51.2 μT and 96.9 μT for coiled wires.